2022
DOI: 10.1021/acs.molpharmaceut.2c00313
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-Labeled Cystine Knot Peptide Targeting Integrin αvβ6 for Lung Cancer PET Imaging

Abstract: Integrin αvβ6 has been considered as a promising biomarker for lung cancer, and its expression is often related to poor prognosis. An αvβ6-binding cystine knot peptide R01-MG was previously engineered and validated. Here, we developed a positron emission tomography (PET) probe of R01-MG for imaging αvβ6-positive lung cancer. Cystine knot peptide R01-MG was synthesized through solid-phase peptide synthesis chemistry and radiolabeled with 68Ga after being conjugated with 1,4,7,10-tetraazacyclododecane-N,N′,N″,N‴… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The α v β 6 integrin has been identified as a significant marker for lung cancer, typically linked to a worse prognosis. Ren et al [ 86 ] created the cystine-knot peptide R01-MG, intended for PET imaging of α v β 6 -positive lung cancer cases. R01-MG was crafted through solid-phase peptide synthesis techniques and labeled with [ 68 Ga]Ga following its conjugation with DOTA, a cyclic compound designed for radiolabeling.…”
Section: Lung Cancer Targeting Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…The α v β 6 integrin has been identified as a significant marker for lung cancer, typically linked to a worse prognosis. Ren et al [ 86 ] created the cystine-knot peptide R01-MG, intended for PET imaging of α v β 6 -positive lung cancer cases. R01-MG was crafted through solid-phase peptide synthesis techniques and labeled with [ 68 Ga]Ga following its conjugation with DOTA, a cyclic compound designed for radiolabeling.…”
Section: Lung Cancer Targeting Probesmentioning
confidence: 99%
“…In vivo PET scans and distribution studies showed that [ 68 Ga]Ga-DOTA-R01-MG was characterized by its quick and efficient uptake in α v β 6-expressing lung tumors, along with swift elimination from non-cancerous tissues, which enhanced the contrast between tumor and normal tissue in images. Conversely, the absence of significant uptake of [ 68 Ga]Ga-DOTA-R01-MG in α v β 6 -negative lung cancer models underscored the probe's targeted specificity towards the α v β 6 integrin [86]. Flechsig et al (2019) investigated the clinical value of SFITGv6, a specific α v β 6 integrin peptide, for the targeted diagnosis of NSCLC.…”
Section: Lung Cancer Targeting Probesmentioning
confidence: 99%
“…Cyclic peptides: A20FMD2 [210] , SFITGv6 [211] , SFLAP3 [212] , c(XAmpRGDX) [213] , c(FRGDLA-Fp [NMe] K) [214] Peptides: RGDLATLRNL [215] , H2009.1 [216] Small molecules: GSK3008348 [217] , PLN-74809 (dual α V β 1 /α V β 6 inhibitor) [191] , arylmorpholines [218] Other: Knotting peptides [219] α V β 8…”
Section: Integrinmentioning
confidence: 99%
“…Several PET tracers, such as arginine-glycine-aspartic (RGD) derivatives targeted-integrin αvβ3 receptors, have been involved in clinical trials and have shown good application value in many types of solid tumors. As a subtype of the integrin family, integrin α6 is expressed on the surface of the cells and acts as a regulator of a variety of cellular functions that are critical to the occurrence, development, and metastasis of solid tumors . Various researchers have reported the potential clinical application value of integrin α6 in many tumor models including for hepatocellular carcinoma (HCC), breast cancer, lung cancer, and colorectal cancer . Richard H. Kimura et al developed an integrin αvβ6 cystine knot PET tracer that can effectively detect multiple cancers in different parts of the body .…”
Section: Introductionmentioning
confidence: 99%